Pemetaan Potensi Seni dan Budaya untuk Mendukung Industri Pariwisata - Nindyo Budi Kumoro; Hipolitus Kristoforus Kewuel; Dhanny S Sutopo; Franciscus Apriwan; Manggala Ismanto; A. Faidlal; Romy Setiawan (Universitas Muhammadiyah Yogyakarta, 2021)
The majority of tourism objects in East Java still rely on artificial and nature-based tourism. As a result, there is an impression that the potential in the society in art and culture has not been optimized for the tourism industry. This service was intended in the context of optimization through exploring the potential of art and culture to support the tourism industry in East Java. This service also aimed to produce mapping data on the potential of cultural arts in the context of creating a directory of arts and culture in Malang Raya. Malang Raya will be used as a pilot project before it can be developed throughout East Java. The data collection method was focused on field studies based on the study of the PPKD (Pokok Pikiran Kebudayaan Daerah) documents for each region, while focus group discussions (FGDs) and field observations were also conducted. The results of the community service program showed that the potential of Malang Raya culture and arts could be compiled online and included in the PPKD mapping document.